Risk factors for hospital admission with RSV bronchiolitis in England: a population-based birth cohort study. - Joanna Murray; Alex Bottle; Mike Sharland; Neena Modi; Paul Aylin; Azeem Majeed; Sonia Saxena; Medicines for Neonates Investigator Group (PLoS ONE)
Objective To examine the timing and duration of RSV bronchiolitis hospital admission among term and preterm infants in England and to identify risk factors for bronchiolitis admission. Design A population-based birth cohort with follow-up to age 1 year, using the Hospital Episode Statistics database. Setting 71 hospitals across England. Participants We identified 296618 individual birth records from 2007/08 and linked to subsequent hospital admission records during the first year of life. Results In our cohort there were 7189 hospital admissions with a diagnosis of bronchiolitis, 24.2 admissions per 1000 infants under 1 year (95%CI 23.7-24.8), of which 15% (1050/7189) were born preterm (47.3 bronchiolitis admissions per 1000 preterm infants (95% CI 44.4-50.2)). The peak age group for bronchiolitis admissions was infants aged 1 month and the median was age 120 days (IQR = 61-209 days). The median length of stay was 1 day (IQR = 0-3). The relative risk (RR) of a bronchiolitis admission was higher among infants with known risk factors for severe RSV infection, including those born preterm (RR = 1.9, 95% CI 1.8-2.0) compared with infants born at term. Other conditions also significantly increased risk of bronchiolitis admission, including Down's syndrome (RR = 2.5, 95% CI 1.7-3.7) and cerebral palsy (RR = 2.4, 95% CI 1.5-4.0). Conclusions Most (85%) of the infants who are admitted to hospital with bronchiolitis in England are born at term, with no known predisposing risk factors for severe RSV infection, although risk of admission is higher in known risk groups. The early age of bronchiolitis admissions has important implications for the potential impact and timing of future active and passive immunisations. More research is needed to explain why babies born with Down's syndrome and cerebral palsy are also at higher risk of hospital admission with RSV bronchiolitis.